Anammox-synchronous zero-valent iron oxidation promoting synergistic nitrogen and phosphorus removal from wastewater. (March 2022) - Zhang, Li; Wang, Yueping; Hao, Shiwei; Dou, Quanhao; Lan, Shuang; Peng, Yongzhen
Highlights: A novel process, annamox–synchronous ZVI oxidation, was developed in this study. The nitrogen and phosphorus removal efficiencies could be increased. PH variation leads to the formation of different types of iron phosphate minerals. The combination of biomass and iron phosphate minerals improves sludge retention. The increase of denitrification functional genes promote the nitrate removal. Abstract: In this study, a novel process, anammox–synchronous zero-valent iron (ZVI) oxidation in which nitrate byproducts are used for in situ  oxidization of ZVI was first developed to simultaneously remove nitrogen and phosphorus from wastewater. The optimal ZVI dosage of 4 g/L significantly improved the nitrogen removal efficiency to 86.02 ± 1.98%, with the highest phosphorus removal efficiency enhanced from 39.62% to 98.97%. Several analytical techniques revealed that iron phosphate minerals formed by biologically induced mineralization promoted the phosphorus removal of the system and enhanced the settleability of granules. Candidatus Brocadia was the main anammox functional bacteria, which could promote the formation of iron phosphorus minerals. The increase of key functional genes involved in denitrification, especially narG, played a pivotal role in reducing nitrate to improve nitrogen removal performance. In addition, abundance regulation of gene fur enabled anammox bacteria always maintain high activity under different pH and ZVI dosages.